A canção e o protesto: do cálice à alegria - Ribeiro, Karina dos Santos (2023)
This work analyzes the role of songs as a form of resistance, struggle, and protest, during the period of the Military Dictatorship in Brazil. During this period, which lasted from 1964 to 1985, political repression and cultural censorship were widely used by the military government as means of controlling and suppressing individual and collective freedoms. Songs, in this context, emerged as a powerful form of expression and resistance, allowing artists and composers to convey critical and challenging messages against the dictatorship. These songs functioned as a tool for raising awareness and popular mobilization, helping to keep the flame of resistance, the fight for civil rights and democracy, alive. Throughout the dissertation, some representative songs from this period were selected and analyzed. “Cálice” by Chico Buarque de Hollanda and Gilberto Gil, “Not to say that I didn’t talk about flowers” by Geraldo Vandré, “Despite you” by Chico Buarque and “Alegria, Alegria” by Caetano Veloso, denounced human rights violations committed by the military regime. The dissertation explores the textual, historical, social, and political context in which the songs were created, examines how the restrictions imposed by the dictatorship shaped musical production and how artists found ways to circumvent censorship to convey their messages. In this sense, the importance of songs as a vehicle of resistance and as a way of preserving the collective memory of a dark period in history stands out, as observed, for example, in the theoretical corpus of Caetano Veloso (2020), Wilberth Salgueiro (2015), Marcos Napolitano (2002) and Marilena Chauí (2017). The research results reveal the relevance and lasting impact of songs against the military dictatorship, and how they influenced culture and art in general, helping to shape the cultural landscape that lasts to this day. These songs played a fundamental role in the formation of political consciousness at the time, and still contribute to popular mobilization, to the day-to-day achievement of democracy. Furthermore, they remain important artistic and historical testimonies, conveying the experiences and emotions of those who fought against oppression. They offer a historical and inspiring foundation for contemporary resistance, reminding us that the courage and determination of those who opposed dictatorships in the past can be a source of strength to challenge injustices today.